Peranan Dana Pihak Ketiga Dalam Kegiatan Usaha Mikro Kecil Dan Menengah Pada Bank Syariah - Wahyu Syarvina (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
Third Party Funds (DPK) may affect the bank's budget. If third party funds increase, then the bank's budget will increase as well. If Third Party Funds decreases, it can weaken the operational activities of sharia banks. The growth of third party funds becomes very important, namely to provide greater financing to prospective customers and also for the development of people's economy, especially in the real sector. Sharia banks are expected to be contributors from financial institutions for economic growth as measured by the growth of the real sector. MSMEs in the Indonesian economy have a very important role in improving the competitiveness of microeconomics. The role of MSMEs is known as a sector that can absorb large labor nationally, accommodate the role of the poor in the economic structure, and is a potentially large sector that contributes to GDP. The government and related parties are obliged to take a leading position in encouraging this sector to grow better. So the economic development of society is getting better, poverty alleviation and unemployment problem can be solved well. Then third party funds in this case should be the concern of each sharia bank.